Bromate Formation Characteristics of UV Irradiation, Hydrogen Peroxide Addition, Ozonation, and Their Combination Processes - Naoyuki Kishimoto; Eri Nakamura (International Journal of Photoenergy)
Bromate formation characteristics of six-physicochemical oxidation processes, UV irradiation, single addition of hydrogen peroxide, ozonation, UV irradiation with hydrogen peroxide addition (UV/H2O2), ozonation with hydrogen peroxide addition (O3/H2O2), and ozonation with UV irradiation (O3/UV) were investigated using 1.88 μM of potassium bromide solution with or without 6.4 μM of 4-chlorobenzoic acid. Bromate was not detected during UV irradiation, single addition of H2O2, and UV/H2O2, whereas ozone-based treatments produced . Hydroxyl radicals played more important role in bromate formation than molecular ozone. Acidification and addition of radical scavengers such as 4-chlorobenzoic acid were effective in inhibiting bromate formation during the ozone-based treatments because of inhibition of hydroxyl radical generation and consumption of hydroxyl radicals, respectively. The H2O2 addition was unable to decompose 4-chlorobenzoic acid, though O3/UV and O3/H2O2 showed the rapid degradation, and UV irradiation and UV/H2O2 showed the slow degradation. Consequently, if the concentration of organic contaminants is low, the UV irradiation and/or UV/H2O2 are applicable to organic contaminants removal without bromate formation. However, if the concentration of organic contaminants is high, O3/H2O2 and O3/UV should be discussed as advanced oxidation processes because of their high organic removal efficiency and low bromate formation potential at the optimum condition.